Emergency Department Increased use of Observation Care for Elderly Medicare Patients - Gabayan, Gelareh Z. (J Hosp Adm, 2018)
BACKGROUND: Over the past decade, a growing number of older Medicare beneficiaries visit the Emergency Department (ED) and have been placed in observation care. We investigated and compared the prevalence and factors associated with patients age ≥ 65 years with Medicare insurance who are placed in the hospital, observation care, or discharged following an ED visit. METHODS: We conducted a retrospective cohort study using data from a nationally representative 5% sample of Medicare patients age ≥ 65 years during the year 2013. We performed multiple generalized estimating equation (GEE) logistic regression analyses to assess the relationship between placement in a hospital vs. discharge, observation care vs. discharge, and observation care vs. admission. RESULTS: Of 537,455 Medicare beneficiaries age ≥ 65 years who visited an ED in 2013, 48.0% (N= 258,083) were discharged, 10.5% (N=56,184) placed in observation care, and 41.5% (N=223,188) were admitted to the inpatient service following the ED visit. The top 2 diagnoses associated with placement in the hospital vs. discharge were ischemic heart disease and renal disease. Patients with symptomatic diagnoses such as chest pain and dizziness were more likely to be placed in observation care following an ED visit as compared to admission to the hospital. CONCLUSION: Compared to prior studies, we found a greater number of older Medicare ED patients placed in observation care and a lower number admitted to the hospital. Most common diagnoses of placement in observation care were symptom-based as compared to being admitted to the hospital which were disease-based.